Propagation characteristics and control technology of blasting vibration in neighborhood tunnel - Zixiu Qin; Yihan Zhao; Lu Chen; Hongtao Cao; Ling Zeng; Wencan Jiao; Hong Xu (Frontiers in Earth Science, 2023)
During the tunnel construction process using the drilling and blasting method, the induced blasting vibration always poses a great threat to the stability and safety of the adjacent tunnel supporting structure. To improve the efficiency and safety of tunnel blasting construction, the vibration propagation and peak particle velocity (PPV) distribution of the lining of an excavated tunnel were investigated during the blasting of an adjacent tunnel located in Guangxi province. The evolution process and distribution characteristics of the PPV of the lining of adjacent tunnels were monitored and analyzed. The results show that the maximum blasting vibration velocity of the lining of the adjacent tunnel can be shown as: PPVx > PPVz > PPVy; hence, the PPVx plays a significant role in the vibration of the adjacent tunnel. According to the tensile stress failure criterion, the PPV threshold was determined to be 12.7 cm/s in this study. To control the damage of surrounding rock induced by the blasting vibration, compound wedge-shaped cutting technology, stress wave dislocation superposition technology, and pre-splitting blasting technology were employed to reduce the impact of blasting vibration on the excavated tunnel.